2019
DOI: 10.1001/jamadermatol.2018.5524
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Vision Loss Following Alexandrite Laser Exposure

Abstract: A woman in her 30s presented with a 1-day history of severe vision deterioration in her right eye. She worked as a nurse in a cosmetic institute and had direct exposure to an alexandrite laser beam the previous day. She directly fixated on the laser probe while calibrating the laser for epilation, and was not wearing eye protection at the time. Her corrected distance visual acuity (CDVA) at presentation was 20/140 in her right eye and 20/20 in her left. She reported similar visual acuity in both eyes prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Our review identified 119 published case reports of ocular injury from lasers and IPL. 11,13,14,16,18–35 , 36–65 Fifty-nine of these cases resulted in a temporary (54 of 59) or permanent (5 of 59) ectropion after CO 2 laser resurfacing where the laser was directed at the eyelids. 13,14,63–65 A 1997 survey of American practitioners performing laser resurfacing found that ectropion occurs in 0.4% of cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review identified 119 published case reports of ocular injury from lasers and IPL. 11,13,14,16,18–35 , 36–65 Fifty-nine of these cases resulted in a temporary (54 of 59) or permanent (5 of 59) ectropion after CO 2 laser resurfacing where the laser was directed at the eyelids. 13,14,63–65 A 1997 survey of American practitioners performing laser resurfacing found that ectropion occurs in 0.4% of cases.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the 60 case reports of direct laser eye injury are shown in Table S1 , Supplemental Digital Content , http://links.lww.com/DSS/B35. 11,16,18–35 , 36–62 Most of the patients were female (55 of 60, 92%), and the age range was 21 to 67 years. The location of eye injury by laser type is demonstrated in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Laser operators should report novel adverse events in the literature and share them with the medical community. 107 -139…”
Section: Discussionmentioning
confidence: 99%